Legitimate interest as legal grounds for processing personal data - Dolenc Dubravka (Bankarstvo, 2020)
The article elaborates the legal basis for data processing provided in Article 12, item 6 of the Law on Personal Data Protection, Official Gazette of the Republic of Serbia no. 87 as of 13 November 2018. The article deals with the comparative advantages of implementing this legal basis in relation to others and provides a practical overview in terms of legitimate interest as an equivalent legal basis to other legal bases of data processing. Examples of good practice of the British Supervisory Authority for Personal Data Protection, as well as the practice of the Agency for Personal Data Protection - the Croatian supervisory authority for data protection - are presented, as well as a significant part of the exceedingly relevant Opinion no. 06/2014 of the Working Party referred to in Article 29 of the cited Directive 95/46 (now the European Data Protection Board). Special attention is given to the so-called LIA, a legitimate interest assessment document and a test of the balance between legitimate interest and the rights and freedoms of individuals, with regard to the processing of personal data. Finally, the article presents the safeguards that must be provided to individuals whose personal data are processed - as well as the need for transparency - in terms of informing individuals of the existence of a legitimate interest, as well as all other necessary information that must be provided to ensure the fair and lawful processing of personal data.